Improvement in quality of frozen Jersey bull semen following fortification with chloroquine diphosphate and ascorbic acid - SINGH, MADHUMEET; SHARMA, AKSHAY (The Indian Journal of Animal Sciences, 2018)
The present study was conducted with an objective of studying the role of certain additives e.g. chloroquine diphosphate and ascorbic acid in maintaining the membrane integrity, viability and motility of spermatozoa at various pre- and post-freezing stages of semen of Jersey bulls maintained under sub-temperate climate. Work was conducted at Sperm Station Palampur, Himachal Pradesh, India, on six apparently healthy pure bred Jersey breeding bulls. A total of 36 ejaculates (6 from each bull), were analysed at six different stages of processing namely neat semen evaluation, post-dilution, post-equilibration, post-thaw and after 1 and 2 h incubation post-thaw at 37Â°C for progressive motility, live dead count, reaction to hypo-osmotic solution and acrosomal integrity, respectively. Evaluation of the semen was done for three groups, i.e. control group (G1), semen fortified with chloroquine diphosphate (G2) and ascorbic acid (G3).The results of the study revealed a significant improvement in progressive motility, live sperm percentage, reaction to hypo-osmotic solution and acrosomal integrity of semen having chloroquine diphosphate (G2) and ascorbic acid (G3) as additives when compared to control group. So, fortification of semen should be done with chloroquine diphosphate and ascorbic acid to improve the quality of semen in future.